Fighting with my family [videorecording (DVD)] - Merchant, Stephen; Merchant, Stephen; Merchant, Stephen; Pugh, Florence, 1996-; Headey, Lena; Frost, Nick, 1970- (Universal Pictures Home Entertainment, 2019)
Tells the story of professional wrestler Paige and her tight-knit wrestling family.